Análise heurística da base de dados Public Medical (PUBMED) - Coelho, Odete Máyra Mesquita (2013)
In the area of Health Sciences, the databases are present since the thirties. With the passage of time they have been innovated by opening wider range of research possibilities, including full text. Among the major bibliographic databases that area, stands the Public Medical, known as PubMed. This database is organized and document production published in scientific journals indexed by the major scientific collections of the world concerning this field of knowledge. After reviewing the methodology of heuristic evaluation we are interested in applying it in the context of this database, seeking response to the following question: Which of the proposed guidelines Nielsen and Tahir (2002) are applied to the usability of human-computer interaction on the basis of PubMed? The objective of this research is to evaluate, with foundation guidelines Nielsen and Tahir (2002), the PubMed interface on the criteria of usability in human-computer interaction. The methodological approach consisted of literature. Then apply the 113 usability guidelines suggested by Nielsen and Tahir (2002) to the environment PubMed. The results show that although these guidelines have been designed to build homepage, twenty eight of them are suited to the PubMed interface. Therefore, it is inferred that these guidelines can be used for the heuristic evaluation of databases. With respect to usability of the database, it became clear that the interface is well structured, friendly and objective, with numerous possibilities of search and information retrieval. Keywords